Surveillance trends of carbapenem-resistant Enterobacteriaceae from Singapore, 2010–2013. Issue 2 (June 2014) - Teo, Jeanette W.P.; Tan, Paul; La, My-Van; Krishnan, Prabha; Tee, Nancy; KOH, Tse Hsien; Deepak, Rama Narayana; TAN, Thean Yen; Jureen, Roland; Lin, Raymond T.P.
Abstract: Trends in carbapenem-resistant Enterobacteriaceae (CRE) collected from hospitals nationwide in Singapore over 3 years are presented. Hospital isolates with imipenem or meropenem minimum inhibitory concentrations (MICs) of >1 mg/L were sent to the National Public Health Laboratory for further investigation. A total of 400 CRE were submitted, 227 (56.8%) of which carried a carbapenemase gene. bla NDM was the most common (130/400; 32.5%), followed by bla OXA-48-like ( bla OXA-48, -181, -232 ) (55/400; 13.8%). Interestingly, four isolates bearing dual carbapenemase genes were also detected. KPC- and OXA-48-like-producing Klebsiella pneumoniae were fingerprinted by DiversiLab ® rep-PCR. Locally, KPC producers do not appear to have clonal dissemination. In contrast, OXA-48-like producers were found to have a greater degree of clustering than KPC producers.